From natural selection to the sentient symphony of life: a chaotic reading of Wertenbaker’s After Darwin - Khalid Ahmad Yas,; Arbaayah Ali Termizi,; Rosli Talif,; Hardev Kaur, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Darwin’s theory of evolution was shaken to the core by the discovery of the second law of thermodynamics and entropy. While it accentuates that the world has evolved from simple to complex, and it moves from disorder to order, the second law preaches the opposite totally. Such inconsistency remains unsolved until the advent of chaos theory, which emphasises that the universe has the capacity to renew itself from within through a process called selforganisation. As a new paradigm shift in science, it pushed scientists to re-read Darwinism from an entirely different perspective. The paper intends to trace the various interpretations of Darwinism in Timberlake Wertenbaker’s After Darwin (1998) through characters’ responses to evolution, utilising chaos theory as a theoretical and methodological framework. The play, which offers a Darwinian-Dawkinsian vision of competition, ends by embracing Margulis and Sagan’s view of cooperation inspired by the new science of chaos. As the only species endowed with an independently functioning brain, Man is able to adapt and turn the table against the brutality of natural selection to establish his own values.